Immunohistochemistry characterization of a bronchioloalveolar carcinoma mixed subtype in cat - Zanoni, Diogo S. [UNESP]; Rivera-Calderón, Luis G. [UNESP]; da Silva, Germana A. [UNESP]; Laufer-Amorim, Renée [UNESP] (Brazilian Journal of Veterinary Pathology, 2017)
A 12 year-old mixed breed female cat was present with signs of dyspnea, cyanosis and drooling, followed by sudden death. At necropsy we observed nodules measuring 0.5 x 0.5 to 2.0 x 2.0 cm in the pulmonary parenchyma showed multifocal atelectasis associated with discrete emphysema. The histopathological examination of lung masses revealed neoplastic epithelial cells compatible with bronchioloalveolar carcinoma (BAC). The immunohistochemical analysis of tumor cells showed positive labeling for pan-Cytokeratin, CK 7, CK 20 and TTF-1. According to macroscopic features, as well as histological and immunohistochemical findings, this tumor was diagnostic as BAC mixed subtype.
Keywords: Feline; Immunohistochemistry; Lung; Neoplasia